Entrepreneurial Intentions and Behaviour as the Creation of Business: Based on the Theory of Planned Behaviour Extension Evidence from Polish Universities and Entrepreneurs - Heydari, Mohammad (2020)
The purpose of this research was to analyze the relationships between the factors that influence entrepreneurial Intention (EI), using a modified version of Ajzen’s theory of planned behaviour (TPB), considering the perception of behaviour. This examination depended on participants' demographic characteristics and psycho-social behavioural traits of attitude (ATT), Subjective norm (SN), and perceived behavioural control (PBC). The establishment of a new business entails various forms of action to achieve desired results. This research analyzes entrepreneurship as the creation of business by engaging in rational behaviour to optimize the use of available technologies and financial sources. These activities are not standardized: They emerge from the entrepreneurial imagination, the perception of new opportunities, and innovation. The aim of a business is not just to produce and sell goods or services. A company must determine the appropriate means of providing them and choose the values to be adopted in the procedure of doing so. Companies should also identify the actions to be taken so that principals or employees incorporate these values into their activities and establish the character that will permit them to regards options and make correct decisions in keeping with the business’s goals.